Early marriages leads to low self-esteem of young girls - Ahmed , Sadaf; Khan, Amna; Noushad , Shamoon; Shah, Nighat; Saleem, Samina; Shershah Syed (International Journal of Endorsing Health Science Research, 2015)
Objective The focus of this study is to be acquainted with the level of trust and reliance regarding reproductive health concerns among early married females. Introduction Many females around the globe are subjected to early marriage with immature minds and bodies, and they are forced to shoulder heavy duties, early pregnancies, harsh family behaviors, family disputes, behavioral problems and understanding problems. Early pregnancies and other health problems have a great impact on their self-esteem, confidence level and their trust on elders to share their problems. When females are married at early age, they are not only deprived of their education but they are also not aware of the health consequences and their solutions. Methods: A cross-sectional observational study was conducted in Karachi and data was collected through detailed interview among 100 subjects (married and unmarried females). Results 41.98% of the unmarried girls relied on lady doctors for their reproductive health problems whereas 37.50% of married girls approached mothers and few talked to lady doctors while most of them were not sharing theirs obstacles with anyone. Conclusion It is concluded that females in their teens before marriage had normal self-esteem and courage to share their problems, on the other hand early marriages were found to cause a decline in their levels of self-esteem due to domestic pressures, less social buck up, fears of in-laws and husbands.